PENERAPAN EVIDENCE BASED NURSING ABDOMINAL MASSAGE TERHADAP KONSTIPASI PADA PASIEN TERPASANG VENTILASI MEKANIK DI RUANG ICU - Thalia Elisabeth (2022)
Intensive care patients are prone to a variety of digestive problems, including damage to the gastrointestinal mucosa. Constipation most often occurs in patients who are attached to mechanical ventilation. Constipation is defined by difficulty in defecation, hard bowel movements, inadequate drainage, or less than three bowel movements per week. Nurses have an important role in overcoming constipation in patients who are installed mechanical ventilation during treatment, one of the nonpharmacological therapies that can be done by nurses to overcome constipation is with abdominal massage. This study aims to find out the application in providing abdominal massage to constipation in patients who are installed mechanical ventilation in the ICU room. Constipation in patients attached to mechanical ventilation can be observed using the Constpation Scoring System. The results of case studies obtained from the application of abdominal massage showed that the patient resolved his constipation problem by being given abdmen massage for 3 days of implementation. It is hoped that in the treatment of patients in the ICU installed mechanical ventilation can apply abdominal massage in overcoming constipation